Motivasi Sembuh Pada Anak Jalanan Korban Penyalahgunaan NAPZA (Studi Kualitatif di Yayasan Balarenik) - Samara, Ghariza A; Wuryaningsih, Caroline Endah (Perilaku dan Promosi Kesehatan : Indonesian Journal of Health Promotion and Behavior, 2022)
Background. Street children are one of the vulnerable groups to become victims of drug abuse. Yayasan Balarenik is one of the Social Rehabilitation Institutions, especially for street children. Drug abusers who are undergoing rehabilitation still have the opportunity to relapse. Relapse behavior in drug abusers can be influenced by various factors, including self-motivation to recover Objective. Determine the motivation of street children to recover from drug abuse at Yayasan Balarenik. Method. This research is a qualitative study. Data collection was collected from October-November 2021 with in-depth interviews with 6 street children, 2 representatives of parents, 1 representative of the Dinkes Provinsi DKI Jakarta, the head of Yayasan Balarenik, and Counselors also Social Workers at Yayasan Balarenik. Results. Friendship environment influenced street children to recognize, use, and obtain drugs. Strong self-will becomes an intrinsic factor for informants to recover from drug abuse. Extrinsic motivational factors came from friends who have stopped using drugs, counselors and social workers' exemplary role and rewards from the Foundation. Brotherhood in the community also became a significant influence. Conclusion. Street children's motivation to recover from drug abuse are from internal encouragement, environmental influences and significant others.